Antiviral Activity of Plant‐Based Additives Against African Swine Fever Virus (ASFV) in Feed Ingredients - Thi Ngoc Ha Lai; Thi Bich Ngoc Trinh; Thi Tam Than; Nguyen Tuan Anh Mai; Niku Moussavi Biuki; Bernhard Eckel; Viktor P. L. Eckel; Thi Lan Nguyen; Van Phan Le (Veterinary Medicine and Science)
ABSTRACT Background African swine fever (ASF) is one of the deadliest swine diseases with haemorrhagic symptoms and a high mortality rate. Plant‐derived additives are potential antiviral agents against viruses due to their environmental and user‐friendly properties. Objectives This study aims to evaluate the efficacy of plant‐based additives (Phyto.A04 and Phyto.B) compared to an organic acid blend (OAB) in inactivating ASF virus (ASFV) in cell culture and feed. Methods ASFV‐spiked feed was treated with individual or combined additives such as OAB, Phyto.A04 and Phyto.B. The viability of ASFV after treatment of ASFV‐spiked feed with additives was then confirmed by both methods, real‐time PCR and cell culture. Results The results of the in vitro test with cell cultures showed that all three additives (OAB, Phyto.A04 and Phyto.B) exerted a strong virucidal effect on ASFV in porcine alveolar macrophage cells. OAB at a concentration of 0.3% reduced the virus concentration from 4.48 log10 HAD50/mL after 1 day of treatment (day 1) to 3.29 log10 HAD50/mL after 3 days of treatment (day 3) and remained undetected after 7 days of treatment (day 7). In Phyto.A04 with 1%, the virus was only detectable on day 1 (3.53 log10 HAD50/mL). Phyto.B with 0.01% and 0.05% both showed good efficacy in completely inhibiting virus presence on days 3 and 7. Conclusions All additives, OAB, Phyto.A04 and Phyto.B, were able to inactivate ASFV in a dose‐dependent manner, as confirmed by cell culture and PCR methods. The combination of additives at different concentrations consistently improved the virucidal results.